Schools and Their English: Language as More than a Medium of Instruction - Narendran, Sathya (Voices of Teachers and Teacher Educators, 2020)
I argue that language reiterates the social position of the speaker and tends to reproduce the structures in society. As such, language in school cannot be viewed simply as a medium of communication or instruction. English in India symbolizes one’s social class. Today, a common perception is that private schools are the sole providers of good English language education. It produces a hierarchy among students who could and could not get into a private school. In this way, social inequality is perpetuated in society through the education system. However this cannot be overcome by simply changing the medium of instruction in all schools to English.